The Effect of Communication and Teamwork on the Effectiveness of Employee Performance at PT. Permodalan Nasional Madani (PNM) Mekaar Unit Kedungwaringin - Neneng Muji Jayanti (PT ARFA DIGITAL TECHNOLOGY, 2025)
Employee performance effectiveness is a strategic element in the operational success of an organization, particularly in socially oriented microfinance institutions such as PT Permodalan Nasional Madani (PNM) Mekaar. This study was prompted by issues of internal miscommunication and weak teamwork that were observed to hinder performance effectiveness at the PNM Mekaar Kedungwaringin Unit. The purpose of this research was to analyze the influence of communication and teamwork on employee performance effectiveness. A quantitative approach with a descriptive and explanatory design was employed. Data were collected through structured questionnaires distributed to all employees (29 respondents) and analyzed using multiple linear regression with SPSS software. The results showed that both communication and teamwork had a positive and significant effect on performance effectiveness, both partially and simultaneously. Open communication and well-coordinated teamwork were found to significantly enhance work efficiency, productivity, and individual contributions to organizational goals. These findings contribute theoretically to the body of knowledge in human resource management and offer practical implications for strengthening managerial strategies in the microfinance sector. The study recommends the implementation of training programs focused on communication and team collaboration, and encourages future research across other units to broaden generalizability.